2021
DOI: 10.1094/pdis-08-20-1703-re
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR and Droplet Digital PCR Are Accurate and Reliable Methods To QuantifyPseudomonas syringaepv.actinidiaeBiovar 3 in Kiwifruit Infected Plantlets

Abstract: Pseudomonas syringae pv. actinidiae (Psa) is the etiological agent of kiwifruit canker disease, causing severe economic losses in kiwifruit production areas around the world. Rapid diagnosis, understanding of bacterial virulence and rate of infection in kiwifruit cultivars is important in applying effective measures of disease control. Psa load in kiwifruit is currently determined by a labor-intense colony counting method with no high-throughput and specific quantification method being validated. In this work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This latter issue would require an internal normalization process to facilitate adjustment for variation between cultivars, but is unavailable for classical growth assays. DNA-based detection as an alternative to classical infection quantification has been deployed for plant-pathogen studies in other pathosystems but has not yet been deployed in the Psa-kiwifruit system until recently (Abdullah et al, 2018;Barrett-Manako et al, 2020;Brouwer et al, 2003;Gallelli et al, 2014;Narusaka et al, 2009;Ross and Somssich, 2016;Weßling and Panstruga, 2012). The use of nucleic acid extraction tools for DNA-based detection has typically been the rate-limiting step for this approach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This latter issue would require an internal normalization process to facilitate adjustment for variation between cultivars, but is unavailable for classical growth assays. DNA-based detection as an alternative to classical infection quantification has been deployed for plant-pathogen studies in other pathosystems but has not yet been deployed in the Psa-kiwifruit system until recently (Abdullah et al, 2018;Barrett-Manako et al, 2020;Brouwer et al, 2003;Gallelli et al, 2014;Narusaka et al, 2009;Ross and Somssich, 2016;Weßling and Panstruga, 2012). The use of nucleic acid extraction tools for DNA-based detection has typically been the rate-limiting step for this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, though, this traditional approach to assessing resistance was achieved in 2 weeks, with significant limitations on the number of plant genotypes (6-12) able to be assessed per run because of labour requirements and time restrictions (Table 1). To increase the throughput of assessing resistance in infected plants, the quantification of Psa3 colonization of the host tissues was also undertaken using a novel DNA extraction method (PDQeX), which simplified and streamlined extraction (Stanton et al, 2019), coupled to previously reported qPCR-based detection (Barrett-Manako et al, 2020). This coupled approach of PDQeX-qPCR for plants sampled at 7 dpi reproduced the resistance in AA07_03 seen by traditional growth assays (Fig.…”
Section: Kiwifruit Cultivars Demonstrate Wide Variation In Their Response To Pseudomonas Syringae Pv Actinidiae Biovar 3 (Psa3)mentioning
confidence: 94%
See 3 more Smart Citations